PROSES MENGUBAH AIR LAUT MENJADI AIR TAWAR MENGGUNAKAN SOLAR CELL DENGAN METODE BOILING - Darpono, Rony; -, Qirom; Niam, Bahrun (Politeknik Harapan Bersama Tegal, 2024)
Seawater is one of the largest natural resources in Indonesia, which contains salt, metals and mycobacteria. Although the resources are abundant, their use is still not widespread, such as being used as clean water or drinking water. Fresh water is very much needed for daily use on ships that are sailing, especially for the dry area, every ship that will go fishing always provides fresh water from land by buying it from PDAM. This study aims to convert sea air into fresh water using the boiling method and solar panel power. Therefore, this method can reduce operating costs when looking for fish in the sea which is actually very easy to get air. In the test from 150 ml of sea water can be obtained to 25 ml with an estimated time of 3 hours, this factor is influenced by the temperature that is not optimal from the DC water heater because it only uses 1 fruit element.